1996
DOI: 10.1083/jcb.134.5.1197
|View full text |Cite
|
Sign up to set email alerts
|

Talin and vinculin play distinct roles in filopodial motility in the neuronal growth cone.

Abstract: Abstract. Filopodial motility is critical for many biological processes, particularly for axon guidance. This motility is based on altering the F-actin-based cytoskeleton, but the mechanisms of how this occurs and the actin-associated proteins that function in this process remain unclear. We investigated two of these proteins found in filopodia, talin and vinculin, by inactivating them in subregions of chick dorsal root ganglia neuronal growth cones and by observing subsequent behavior by video-enhanced micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
104
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 43 publications
9
104
0
Order By: Relevance
“…These observations resemble the finding that disruption of myosin IIA reduced cell adhesion of mouse neuroblastoma cells (Wylie and Chantler, 2001). Furthermore, CALI of vinculin, a component of focal contacts, in growth cones also caused filopodia to detach and buckle (Sydor et al, 1996). Thus, myosin II inhibition with blebbistatin may disrupt adhesion of filopodia, and we speculate the increased filopodial extension rates are attributable to reduced membrane cortical tension and altered actin dynamics (Mallavarapu and Mitchison, 1999;Raucher and Sheetz, 2000).…”
Section: -D ( S)-(ϫ)-supporting
confidence: 63%
“…These observations resemble the finding that disruption of myosin IIA reduced cell adhesion of mouse neuroblastoma cells (Wylie and Chantler, 2001). Furthermore, CALI of vinculin, a component of focal contacts, in growth cones also caused filopodia to detach and buckle (Sydor et al, 1996). Thus, myosin II inhibition with blebbistatin may disrupt adhesion of filopodia, and we speculate the increased filopodial extension rates are attributable to reduced membrane cortical tension and altered actin dynamics (Mallavarapu and Mitchison, 1999;Raucher and Sheetz, 2000).…”
Section: -D ( S)-(ϫ)-supporting
confidence: 63%
“…Associated with focal adhesions and focal complexes are numerous signaling proteins including FAK, and structural proteins including paxillin and vinculin (41,45,46). When cells adhered to fibronectin or laminin, paxillin and talin are found in typical focal adhesion structures distributed over the cell bodies, as previously reported (30,44,47) (Fig.…”
Section: Fibroblast Adhesion To Cyr61 or Ctgf Induces Extensive And Psupporting
confidence: 57%
“…In situ experiments using chromophore-assisted laser inactivation (CALI) have implicated talin as a crucial molecule in the ECMactin linkage during filopodial extension and retraction (Sydor et al, 1996). More recently, extensive characterization of actin dynamics using fluorescent speckle microscopy (FSM) (Waterman-Storer et al, 1998) has revealed two spatially, kinetically and kinematically distinct actin networks; with the local expansion of the lamella network being a source of persistent cell protrusion (Ponti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%